Analisis Kadar Kalium (K) Dan Kalsium (Ca) Dalam Kulit Dan Daging Buah Terung Kopek Ungu (Solanum melongena) Asal Desa Nupa Bomba Kecamatan Tanantovea Kabupaten Donggala - Rahmelia, Deskriana; Diah, Anang Wahid M.; Said, Irwan (Jurnal Akademika Kimia, 2015)
This study aims to determine the levels of potassium (K) and calcium (Ca) in the rind and flesh of the kopek purple eggplant (solanum melongena) fruit. Determination of mineral level was done by destruction of the sample using stong acids, which were nitric acid (HNO3) and perchloric acid (HClO4). The method used in this study was a laboratory experiment using a flame photometry. The results showed that the levels of potassium in the flesh of kopek purple eggplant farmers I and II were 215 ± 7,07 mg/100 g and 195 ± 14,14 mg/100 g, respectively; while the rind of kopek purple eggplant farmers I and II were 142,5 ± 3.53 mg/100 g and 102.50 ± 3.53 mg/100 g, respectively. The levels of calcium in the flesh of kopek purple eggplant farmers I and II were 10 ± 7.07 mg/100g and 15 ± 3.53 mg/100 g, respectively; while the rind of the kopek purple eggplant farmers I and II were 6.25 ± 1.76 mg/100 g and 7.50 ± 3.53 mg/100 g, respectively.